PERBEDAAN MASSAGE DAN KOMPRES AIR HANGAT DALAM MENURUNKAN NYERI PERSALINAN KALA 1 - Tanti Fitriyani; Vriska Roro Sekar Arum; Tri Endah Widi Lestari (Ensiklopedia of Journal, 2026)
An essential component of labor and delivery is labor discomfort.  The force of the contractions and the pressure created are what cause the first stage of discomfort.  The intensity of the pain increases with the degree of abdominal distension.  Unbearable pain might prevent the mother from pushing, which can prolong labor and cause fetal discomfort.  The purpose of this study was to compare the effects of warm compresses and massage on first-stage labor pain. The study employed an external comparison group, a before-and-after intervention strategy, and a quasi-experimental methodology.  Forty women in the first stage of labor were selected by accidental selection from a population of sixty-five women giving delivery. Observation sheets were employed as data collecting methods, and paired and unpaired t-tests were performed for data analysis. With a mean pain scale score of 1.5 for the massage group and 0.57 for the warm compress group in the pre-test–post-test, the findings demonstrated that massage was superior to warm compresses in lowering first-stage labor pain. In an attempt to lessen labor pain, health professionals who assist with childbirth are expected to employ massage techniques. Keywords       : Massage, warm compress, labor PainLiteratures     : 27 (2010- 2019)